2017
DOI: 10.1038/s41598-017-16854-9
|View full text |Cite
|
Sign up to set email alerts
|

The importance of parameter choice in modelling dynamics of the eye lens

Abstract: The lens provides refractive power to the eye and is capable of altering ocular focus in response to visual demand. This capacity diminishes with age. Current biomedical technologies, which seek to design an implant lens capable of replicating the function of the biological lens, are unable as yet to provide such an implant with the requisite optical quality or ability to change the focussing power of the eye. This is because the mechanism of altering focus, termed accommodation, is not fully understood and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 65 publications
2
34
0
Order By: Relevance
“…Gross lens shape change caused by strain results microstructural level changes in all the regions of the lens that we examined. This provides critical information that will be useful in expanding current biomechanical models of lens shape changes (Reilly and Ravi, 2010;Reilly, 2014;Wang et al, 2017). Furthermore, the identification of a relationship between microstructure and tissue biomechanics supports the idea that age-dependent microstructural alterations, such as an increase in stiffness of cells or matrix (Starodubtseva, 2011;Lacolley et al, 2017), could have biomechanical consequences at the tissue level.…”
Section: Discussionsupporting
confidence: 53%
“…Gross lens shape change caused by strain results microstructural level changes in all the regions of the lens that we examined. This provides critical information that will be useful in expanding current biomechanical models of lens shape changes (Reilly and Ravi, 2010;Reilly, 2014;Wang et al, 2017). Furthermore, the identification of a relationship between microstructure and tissue biomechanics supports the idea that age-dependent microstructural alterations, such as an increase in stiffness of cells or matrix (Starodubtseva, 2011;Lacolley et al, 2017), could have biomechanical consequences at the tissue level.…”
Section: Discussionsupporting
confidence: 53%
“…Young's modulus E or shear modulus G. This log-log linear equation [25] is described as: log( ) = log( ) + (3) where a and b are material dependent coefficients that were determined for porcine lenses: a=0.093 and b=9.29 [25] which have similar elastic shear moduli to young human lenses [29], [reviewed in 30]. Taking the eye lens as nearly incompressible [31], [32] Young's and shear modulus can be linearly related: E=3G [10], [30]. The calculated Young's moduli E at the central plateau and at the lens poles are 0.82 kPa and 0.04 kPa respectively.…”
Section: Materials Properties and Opto-mechanical Couplingmentioning
confidence: 99%
“…Yet a number of modelling approaches simplify these forces as emanating from a single point [5], [6], [7], [8], [9]. Recently it was shown that separating directions of zonular force across the three sections makes a substantial difference to the shape change and renders the modelled simulation closer to the changes in shape seen in the biological lens [10]. This is fundamental for understanding the mechanical behaviour of the different zonular sections and for providing insights needed to understand the accommodative process and its loss with age.…”
mentioning
confidence: 99%
See 2 more Smart Citations